Effect of fish meal quality on the growth performance of weanling pigs - G R Stoner; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1989)
The objective of this experiment was to evaluate three fish meal sources added to diets for the early-weaned pig. Fish meal sources were analyzed for total volatile nitrogen (TVN), which is an indicator of protein degradation of the raw material. Regardless of TVN content, pigs fed diets containing fish meal had better average daily gain (ADG) and average daily feed intake (ADFI) than pigs fed a diet without added fish meal. However, TVN content and chemical digestibility estimates of fish meal were associated with growth performance of starter pigs. Feed intake increased as TVN content increased. Although ADG was not influenced by TVN, feed conversion was less efficient, and thus, the cost of gain was increased as TVN content increased. Conversely, the cost of gain decreased as the chemical digestibility increased. The results of this study suggest that chemical digestibility and TVN content of different fish meal samples are indicative of their relative quality. However, maximum TVN content and minimum chemical digestibility values to indicate a high quality fish meal have not been determined.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Pig; Fish meal; Performance; Early weaning